Untangling Community Assembly Through Functional Traits and Phylogenetic Alpha Diversity in Subtropical Karst Forests - Shichu Liang; Miao Dong; Yong Jiang; Daniel F. Petticord; Junwei Li; Jianghui Long; Quan Su (Ecology and Evolution)
ABSTRACT Taxonomic diversity is insufficient to fully characterize species co‐existence in forest ecosystems. Incorporating trait‐based and phylogenetic data into studies of communities provides insight into the mechanisms by which coexistence emerges and is maintained in forest landscapes. We integrated trait‐based and phylogenetic models of community structure to gain insight into community processes in deciduous, mixed, and evergreen forests. We also explored how phylogenetic community structure may vary across environmental gradients within deciduous, mixed, and evergreen forests using a null model approach. Plants appeared to transition from being acquisitive within dry, deciduous forest plots atop fertile soils to becoming more conservative in moist, infertile soil conditions in evergreen forests. We present this as strong evidence of environmental filtering mediating plant community composition. Our models suggest a strong influence of environmental filtering in deciduous forests and competitive exclusion and random processes in mixed and evergreen settings. Besides, thicker leaves, lower SLA, and higher WD in evergreen forests than deciduous forests may reflect adaptation to chronic herbivore pressure—a key biotic filter shaping trait distribution in different forest systems. Our results suggest that phylogeny and functional traits represent different lenses through which one may view community assembly, which should be viewed independently of each other. We suggest future research incorporating both phylogenetic and trait‐based perspectives, and possibly even more axes (stress tolerance, etc.) is necessary to provide insight into community assembly.